(untitled) (Bangladesh Veterinarian, 2010)
The effects of different sources of nitrogen on yield, chemical composition and nutritive value of Dal grass (Hymenachne amplexicaulis) were measured. Control (T0) had no fertilizer; T1 was treated with urea - 240 kg N/ha; T2 with cow manure-25.8 tonnes (t)/ha; T3 with goat manure-13.2 t/ha; T4 with rabbit manure-7.6 t/ha and T5 with poultry manure-5.9 t/ha. All treatments provided the same amount of nitrogen. Experiment was conducted following completely randomized design (CRD) with four replications in each treatment. In the first cutting maximum green forage (33.3 & 31.1), dry matter (7.7 & 7.1) and organic matter (7.1 & 6.5) MT/ha were obtained (p<0.01) for the treatments of urea and poultry droppings. In second cutting, poultry manure showed higher value (p<0.01) than other treatments for green forage (27.8), dry matter (DM; 5.3), organic matter (OM; 4.9) and crude protein (CP; 0.6). In first cutting, urea showed higher DM (23.0) and EE (2.1) than other nitrogen sources. On the other hand, rabbit manure showed higher nitrogen free extract (NFE) (46.8) than other treatments. For crude fibre (CF) and ash, no significant difference was observed between treatments. In second cutting, poultry manure showed higher DM (19.1) and EE (3.7). In both cuttings, urea gave higher CP (11.2 and 12.1) than other nitrogen sources. CF was not significantly different (p>0.05) for second cutting. Control group showed higher (9.9) and NFE (48.2) than other treatments. There was no significant (p>0.05) difference in organic matter digestibility and metabolizable energy content of Dal grass between treatments. It is suggested that poultry manure may be recommended as a source of nitrogen fertilizer for Dal grass production in Bangladesh. DOI: 10.3329/bvet.v25i2.4621 Bangl. vet. 2008. Vol. 25, No. 2, 75-81